Upaya Guru Pendidikan Agama Islam dalam Mengembangkan Akhlakul Karimah di SMP Muhammadiyah 7 Surakarta - Yusuf Effendy; Hafidz (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
The purpose of this research is to find out and understand what efforts are made by Islamic Religious Education teachers at SMP Muhammadiyah 7 Surakarta to realize the school's vision and mission in developing students' morals and morals. This research uses a descriptive qualitative method, using a descriptive qualitative approach to understand phenomena related to the research subject. Data collection in this research was carried out by observation and interviews. To ensure the validity of the data, researchers used triangulation. Data analysis was carried out through data reduction, presentation and drawing conclusions. Based on the results and discussion in this research, the Islamic Religious Education Teacher at SMP Muhammadiyah 7 Surakarta made various efforts to develop morals in accordance with the school's vision and mission. The efforts made include five points, namely 1) Teachers provide role models, 2) Carry out habituation activities, 3) teach morals, 4) teachers provide motivation, and 5) provide rewards and punishment.